The Moderating Effect of Sharia Stock Index Inclusion on the Relationship Between Sustainability Performance and Profitability - Ariana, Nadya; Dewi, Miranti Kartika (E-Jurnal Akuntansi, 2024)
This study examines the relationship between sustainability performance and profitability, with a specific focus on the moderating role of inclusion in the Sharia Stock Index. The index's screening criteria are hypothesized to align with sustainability objectives, potentially enhancing firm profitability. The analysis is based on a sample of 75 firms from Indonesia and Malaysia over the period 2018–2022. Using panel data regression, the findings reveal a positive relationship between overall ESG (Environmental, Social, and Governance) scores and profitability. However, no significant relationship is identified between individual ESG pillar scores and profitability. Additionally, the moderating effect of Sharia Stock Index inclusion on the sustainability performance–profitability relationship is not supported by the results. This study contributes to the literature by exploring the interplay between sustainability performance and profitability within the context of Muslim-majority ASEAN countries. It also challenges assumptions regarding the role of Sharia Stock Index inclusion, offering fresh insights for investors and policymakers aiming to balance sustainability objectives with financial performance.